Global database of factors influencing the adoption of diversified farming systems - Sanchez Bogado, Andrea Cecilia (2024)
We present a global dataset documenting the effect of factors on the adoption of diversified farming systems compiled through a systematic review of primary studies. The dataset includes 1,979 effect sizes from 153 primary peer-reviewed studies It contains evidence from the effect of the impact of 63 factors across eight key categories—biophysical context, farmers’ attitudes, political and institutional context (access to knowledge, land tenure, financial risk management), and five forms of capital (financial, human, natural, physical, and social)—on the adoption of ten diversified practices. Data collection and reporting follows the best standards for systematic reviews and is specifically designed for use in meta-analysis.